COMPUTER MODELING OF DYNAMICS OF THE UQUID PHASE MOVING IN INGOT OF ROUND CUT, HEING CRYSTALLIZED IN MNLZ - A. N. Chichko; N. V. Andrianov; A. V. Demin; D. M. Kukuj; V. F. Sobolev; Ju. V. Jatskevieh; O. I. Chichko (Литьë и металлургия)
Computer modeling of the liquid phase length of the ingot moving in MNLZ with predetermined speed on the basis of three-dimensional equation of heat conduction and models, considering changing of carbon concentration in liquid and solid phase at crystallization, is described. There are determined effective lengths of stretch of the liquid phase which can be formed in slug with circular section.